Does Postoperative Gabapentin Administration Reduce Opioid Consumption after Foot and Ankle Surgery?. Issue 2 (2nd July 2020) - McKissack, Haley; He, Jun Kit; Naranje, Sameer; Washington, Joshua L.; Patel, Romil K.; Ray, Jessyca; McGwin, Gerald; Johnson, Michael D.; Shah, Ashish
Category: Ankle; Hindfoot; Midfoot/Forefoot Introduction/Purpose: Prescription opioids are commonly used to control postoperative pain in foot and ankle surgery, but present potentially detrimental side effects including sedation, respiratory depression, and addiction. In foot and ankle surgery, pain is a common cause of delayed hospital discharge and decreased willingness to move, thereby slowing recovery. Gabapentin acts by decreasing lesion-induced hyperexcitability of posterior horn neurons and central sensitization, and has been explored as a potential addition to patients' pain regimen. Although studies have previously assessed the effect of gabapentin on pain relief, to our knowledge none have evaluated whether gabapentin is effective in opioid consumption reduction beyond the immediate postoperative period. The purpose of this study is to assess whether gabapentin acts synergistically to improve postoperative pain among patients undergoing foot and ankle surgery. Methods: Patients from a single institution who underwent elective foot and ankle surgery were identified using CPT codes 27700, 27702, 27870, 28705, 28715, 28725, 28730, and 28740. All patients prescribed opioids postoperatively were included. A retrospective chart review was conducted for each patient to identify prescription dose, number of pills, date in which prescription was filled, and dates of refills for oxycodone, hydrocodone, oxycodone-acetaminophen, hydrocodone-acetaminophen, tramadol, and gabapentin. Medication information was collected only for prescriptions by the operating surgeon, nurse practitioner, physician assistant, resident, or fellow which were pertinent to the foot/ankle surgery performed; prescriptions from other services or providers were not included in order to ensure that the medications prescribed were specific to postoperative pain. Opioid quantities were converted to morphine equivalents and compared at various time intervals between patients who were prescribed only opioids, and patients who were prescribed opioids and gabapentin. Results: Among patients not taking opioids or gabapentin preoperatively, total morphine equivalents prescribed was significantly less among patients prescribed postoperative gabapentin (177.3 OME) in comparison to those prescribed only opioids (442.2 OME) (p=0.0018) in the 3-6 week postoperative interval. When all patients were analyzed, including those taking preoperative opioids or gabapentin, patients who received postoperative gabapentin were also prescribed significantly fewer OME at weeks 1-2 (p= 0.0270), weeks 3-6 (p = 0.0006), and weeks 7 - 12 (p = 0.0149). Conclusion: Gabapentin may be effective in reducing postoperative opioid consumption beyond the immediate postoperative period among elective foot and ankle surgery patients. Prospective clinical trials are warranted to further validate these results.